Hadis tentang Berhubungan Badan di Luar Pernikahan - Salis Abdalah Hatami (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss how the explanation of having sex outside of marriage in the perspective of hadith. This research uses qualitative type method with content analysis through literature study. The results and discussion in this study include a general view of adultery, takhrij sanad in the hadith regarding adultery, and how to explain the prohibition of adultery. The conclusion of this study shows that adultery is a behavior that is prohibited both religiously and legally in Indonesia, and the hadith that explains the prohibition of adultery is a saheeh hadith. This study warns of the dangers and other negative impacts of adultery.